Method Validation for Quantification of PFOS and PFOA in Human Plasma and a Pilot Study in Blood Donors from Thai Red Cross Society - Teerapong Lertassavakorn; Nanthanit Pholphana; Nuchanart Rangkadilok; Tawit Suriyo; Punthip Teeyapant; Jutamaad Satayavivad (Toxics, 2023)
Information regarding per- and polyfluorinated substances concentrations in biological samples from the Thai population was still lacking. A sensitive bioanalytical method was developed and validated for the quantification of perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) levels in human plasma. Simple protein precipitation and LC–MS/MS techniques were used with stable isotope internal standards of 13C8–PFOS and 13C8–PFOA. The validated method followed the ICH bioanalytical validation guideline, and the results showed good accuracy, precision, and reproducibility. The validated analytical method was then applied to determine PFOS and PFOA concentrations in 50 human plasma samples from the National Blood Center, Thai Red Cross Society. The concentrations were found to be in ranges of <0.91–6.27 ng/mL for PFOS and <0.49–2.72 ng/mL for PFOA. PFOS was also measured separately for its isomers, and the geometric means of the linear isomer (L–PFOS) and branched isomer (br–PFOS) in plasma samples were at 1.85 and 0.41 ng/mL, respectively. Both PFOS and PFOA concentrations were lower in comparison to previous reports from other countries. The present study showed the application of our reliable method to determine PFOS and PFOA in biological samples in order to monitor the human exposure of both chemicals in Thailand.